A New Look at the TOR Anonymous Communication System - Imran Ahmad; M. Saddique; U. Pirzada; M. Zohaib; A. Ali; M. Khan (Journal of Digital Information Management, 2018)

A New Look at the TOR Anonymous Communication System- - Imran Ahmad; M. Saddique; U. Pirzada; M. Zohaib; A. Ali; M. Khan (Journal of Digital Information Management, 2018)
Whenever a user tries communicating with another recipient on the Internet, vibrant information is sent over different networks until the information is intercepted or normally reaches the recipient. Precarious information crisscrossing networks is usually encrypted. In order to conceal the sender’s identity, different implementations have proven successful - one of which is the invention of anonymous communication systems. There are many anonymous communication systems developed but, the Onion Router (Tor) is the greatest organized anonymous communication system, which offers online anonymity and privacy. There are a vast number of obstacles in security that have to be considered when deploying Tor. This paper thoroughly investigates and presents these security issues in Tor.